Rationalizing the Role of Monosodium Glutamate in the Protein Aggregation Through Biophysical Approaches: Potential Impact on Neurodegeneration - Ahanger, Ishfaq Ahmad; Bashir, Sania; Parray, Zahoor Ahmad; Alajmi, Mohamed F.; Hussain, Afzal; Ahmad, Faizan; Hassan, Md. Imtaiyaz; Islam, Asimul; Sharma, Anurag (Frontiers in Neuroscience, 2021)
Monosodium glutamate (MSG) is the world’s most extensively used food additive and is generally recognized as safe according to the FDA. However, it is well reported that MSG is associated with a number of neurological diseases, and in turn, neurological diseases are associated with protein aggregation. This study rationalized the role of MSG in protein aggregation using different biophysical techniques such as absorption, far-UV CD, DLS, and ITC. Kinetic measurements revealed that MSG causes significant enhancement of aggregation of BSA through a nucleation-dependent polymerization mechanism. Also, CTAB-BSA aggregation is enhanced by MSG significantly. MSG-induced BSA aggregation also exhibits the formation of irreversible aggregates, temperature dependence, non-Arrhenius behavior, and enhancement of hydrodynamic diameter. From the isothermal titration calorimetry measurement, the significant endothermic heat of the interaction of BSA-MSG indicates that protein aggregation may be due to the coupling of MSG with the protein. The determined enthalpy change (ΔH) is largely positive, also suggesting an endothermic nature, whereas entropy change (ΔS) is positive and Gibbs free energy change (ΔG) is largely negative, suggesting the spontaneous nature of the interaction. Furthermore, even a low concentration of MSG is involved in the unfolding of the secondary structure of protein with the disappearance of original peaks and the formation of a unique peak in the far-UV CD, which is an attention-grabbing observation. This is the first investigation which links the dietary MSG with protein aggregation and thus will be very instrumental in understanding the mechanism of various MSG-related human physiological as well as neurological diseases.